Corruption: a comparison between Singapore and Malaysian legal regime / Halil Paino, Khairul Anuar Abdul Hadi and Nafsiah Mohamed. - Paino, Halil; Abdul Hadi, Khairul Anuar; Mohamed, Nafsiah (Universiti Teknologi MARA Cawangan Selangor, 2016)
Corruption is a global problem. Without effective legal regime, corruption would cost economic, political, and social instability. Based on the International Transparency perspective index on corruption, Singapore ranked 8 as less corrupt nation and scored 85 out of 100 based on the transparency index. These data show Singapore as a leading country in fighting corruption in South East Asia region. Therefore, this paper intends to examine the legal regime in Malaysia and Singapore in order to identify the legal gap and propose an improvement and comprehensive legal framework against corruption.